Irska - Kumer, Peter (Vodniki LGD, 2015)
Whenever anyone mentions Ireland, the first things that leap to mind are the rolling green landscape, picturesque castles, and cheerful Irish people hanging out in pubs, listening to good music and drinking Guinness. These are typical scenes from various movies set on the "emerald isle," as the poet William Drennan poetically called it. Ireland has a long and complicated history. Until the end of the Middle Ages, it was characterized by Celtic culture, Viking raids, and the Norman invasion, and the entire Modern Age was marked by the dispute between the British and the Irish over control of the island-and many bloody conflicts between the two. It was only in the twentieth century that the situation calmed down to some extent, and the island was divided into the independent Republic of Ireland and British Northern Ireland.